Tough protein organohydrogels. Issue 45 (16th October 2018) - Zhou, Dan; Chen, Fan; Wang, Jiahui; Li, Tianzhen; Li, Baijia; Zhang, Jie; Zhou, Xiaohu; Gan, Tiansheng; Handschuh-Wang, Stephan; Zhou, Xuechang
Abstract : Tough protein organohydrogels are fabricated by applying a solvent displacement-induced toughening (SDIT) strategy. By one-step SDIT, relatively weak and brittle protein hydrogels change to protein organohydrogels with remarkably high performance in anti-freezing, non-drying, topological healing, thermal plasticizing, mechanical toughness and stretchability. Abstract : Tough protein organohydrogels were fabricated by applying a solvent displacement-induced toughening (SDIT) strategy. With SDIT, traditionally weak and brittle protein hydrogels were altered to protein organohydrogels with remarkably high performance in anti-freezing, non-drying, topological healing, thermal plasticizing, mechanical toughness and stretchability. The SDIT opens a reliable and straightforward path to develop novel biomimetic materials and artificial devices from abandunt protein-based sources.